Evaluation of paracheck - Pf™ rapid malaria diagnostic test for the diagnosis of malaria among HIV-positive patients in Ibadan, South-Western Nigeria (2013)
Febrile illnesses occur frequently among HIV positive patients and these are often treated presumptively as malaria in endemic areas. Parasite-based diagnosis of malaria will eliminate unnecessary treatment, reduce drug–drug interactions and the chances for the emergence of drug resistant Plasmodium. We evaluated finger prick blood samples from 387 people living with HIV (PLWHIV) and suspected of having malaria by expert microscopy and Paracheck-Pf TM – a histidine-rich protein-II based malaria rapid diagnostic test. The study was conducted at the PEPFAR supported AIDS Prevention Initiative in Nigeria (APIN) Clinic of the University College Hospital Ibadan, southwest Nigeria. Outcome parameters were prevalence of malaria parasitemia, sensitivity and specificity of Paracheck-Pf as well as the positive and negative predictive values for Paracheck-Pf using microscopy of Giemsa-stained blood film as gold standard. Malaria parasites were detected in 19.1% (74/387) of enrollees by microscopy and 19.3% (74/383) by Paracheck-Pf. Geometric mean parasite density was 501/µl (range 39–749 202/µl). Sensitivity and specificity of Paracheck-Pf at all parasite densities were 55.4% and 89.3% while corresponding figures at parasite densities ≥200/µl were 90.9% and 90.3%. Sensitivity and specificity at parasite densities ≥500/µl was 97.6% and 90.3%. Positive and negative predictive values for parasite density ≥200/µl were 55.4% and 98.7%, respectively. Paracheck-pf was found to be a useful malaria diagnostic tool at parasite densities ≥200/µl facilitating appropriate clinical management.